Orbital cellulitis from untreated conjunctival wound - Aimy Mastura Zurairah Yusof,; Norshamsiah Md. Din,; Hazlita Mohd Isa,; Othmaliza Othman,; Ropilah Abdul Rahman, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Orbital cellulitis is a potential blinding condition resulting from infection of the orbital contents, including the optic nerve. It may be fatal in cases with extension into the optic canal and subsequently the brain. Common aetiologies include extension of infection from paranasal sinusitis or preseptal cellulitis. This case report depicts the unusual occurrence of orbital cellulitis following a trivial superficial conjunctiva laceration wound from a motor-vehicle accident. Aggressive treatment with systemic antibiotics resulted in good visual outcome. All wound on or around the globe must be diligently treated to prevent such detrimental complication.